The Roles of Non-Monetory Benefit, Pay, Nature of Work and Recognition Towards Job Satisfaction Among Employee in Manufacturing Company in Penang - Nor Laila, Hussain (2012)
The job satisfaction is necessary to promote functional employee behaviours. The job satisfaction of its workers means a work force that is motivated and committed to high quality performance for their work. Job satisfaction can be an important indicator of how employees feel about their jobs and a predictor of work behaviours. And, securing commitment and retaining good employees are very important to achieve stability and reduce costly turn over in every company. Therefore, the purpose of this study is to identify the roles of non-monetary benefit, pay, nature of work and recognition towards job satisfaction among employees in the manufacturing company in Penang. The data were analysed using “statistical Package for Social Sciences” (SPSS version 20). Statistical techniques used were as Pearson correlation, Simple Regression and ANOVA test to determine the relationships of variables. A total of 92 of questionnaires were distributed to respondents at their places of work, then completed and returned by respondents. Using 5 likert of scale containing five choices from 1 (Strongly Agree) to 5 (Strongly Disagree) using to associate the variables of dependence and independence. The results indicate that employees at manufacturing companies in Penang expressed that the roles of nature of work emerged as major source of satisfaction, followed by pay. The non-monetary benefit and recognition are the third and fourth important factors to satisfy the employee’s in their daily work. The overall conclusion stated that there are positively relationships between the four independence variable toward dependent variable, job satisfaction among employee in manufacturing company. From this study, the finding contributes the outcome of the study as a guideline for managerial to identify and understand the employee job satisfaction after identify the main job satisfier and relate the job satisfaction variables in the company.